The problem solution of the Surface-to-air missile systems electronic equipment durability prediction when implementing the strategy of condition-based maintenance and repair using the Group Method of Data Handling - Open’ko , Pavlo; Kobzev , Vladyslav; Larin, Volodymyr; Drannyk , Pavlo; Tkachev , Volodymyr; Uhrynovych, Oleh (Social Development and Security, 2021)
The possibilities of application of known methods for estimating the life to the task of forecasting the ultimate state of radio-electronic means of the surface-to-air missile system during the operation status of the requested technical. A procedure for constructing a mathematical model of change of reliability in service with the Group Method of Data Handling, which is more fully into account the specific characteristics of radio-electronic means of the surface-to-air missile system and considers the possibility of use as basic data for the creation of models not uniformly precise results of estimation of an indicator of non-equal exact measuring to operational supervision.